3,4-Dihydroxyphenylalanine (dopa) decarboxylase activity in the arthropod nervous system - Murdock, L. L. (1973)
1. When homogenates of brains from mature adult locusts (Locusta migratoria) were incubated with l-3-(3,4-dihydroxyphenyl)[3-(14)C]alanine the major radioactive metabolite was dopamine, suggesting the presence of a dopa (3,4-dihydroxyphenylalanine) decarboxylase. 2. Decarboxylation of l-dopa by this tissue, measured under optimum conditions by a radiochemical method, was 21μmol of CO(2)/h per g wet wt. Apparent decarboxylation of l-tyrosine proceeded at 0.34μmol of CO(2)/h per g wet wt. There was no detectable decarboxylation of l-tryptophan, l-histidine or l-phenylalanine. 3. Dopa decarboxylase activity was found in all major regions of the ventral nerve cord of the mature locust (range: 4–7μmol of CO(2)/h per g wet wt.) but was low or absent in thoracic peripheral nerve. 4. Marked decarboxylation of l-dopa was found in homogenates of brains of four other species of insects, and in brain and ventral nerve cord, but not in the claw nerve, of the crayfish. 5. The activity of the locust brain enzyme may be slightly lower at the time of imaginal ecdysis than during the mature period. By contrast, the dopa decarboxylase that produces dopamine as an intermediate in cuticle biosynthesis is known to be high in activity at the time of ecdysis and low in activity during the intermoult stages.